Causes of job turnover in the public school superintendency: An explanatory analysis in the western United States - Melver, Toby A (ProQuest Dissertations & Theses, 2011)
The purpose of this mixed-methods study was to determine the factors that affect public school superintendent turnover in five western states. An explanatory theory was developed to cover all of the possible variables and show the relationship between those variables. The questions that guided this research study were: (1) What environmental factors influence the tenure of superintendents in western states? (2) What governance factors influence the tenure of superintendents in western states? (3) What personal factors influence the tenure of superintendents in western states? (4) What are the incentives and/or disincentives that influence the tenure of superintendents in western states? Quantitative data were collected using an internet based survey sent to 400 superintendents in five western states. Subjects were selected based on the size of their school district (2,000 -10,000 students). Qualitative data were collected through personal interviews with eight long-serving (7+ years) superintendents from the survey pool. Interviews were analyzed and coded using Auerbach and Silverstein's six-step qualitative data coding method. The researcher found that governance factors (ie. relationship with school board, role conflict) were the leading factors in determining superintendent tenure. The researcher found that possession of high-functioning communication skills by the superintendent aids in the length of tenure. For aspiring superintendents, the understanding of the complexity of the superintendent position was found to be important before entering the superintendency, as the complex nature of the job can be overwhelming for those superintendents who are not aware of the varying aspects of this position.